2016
DOI: 10.18047/poljo.22.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of red clover (Trifolium pratense L.) productivity in environmental stress

Abstract: Assessment of red clover (Trifolium pratense L.) productivity in environmental stressProcjena proizvodnoga potencijala crvene djeteline (Trifolium pratense L.) u uvjetima okolišnoga stresa Tucak, M., Popović, S., Čupić, T., Krizmanić, G., Španić, V., Meglič, V., Radović , J. Original scientific paper Izvorni znanstveni članak ASSESSMENT OF RED CLOVER (TRIFOLIUM PRATENSE L.) PRODUCTIVITY IN ENVIRONMENTAL STRESS SUMMARYThe frequency of extreme climatic events has increased due to global climate change. The obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…It is a short-term perennial legume that grows for about two to three years and is adapted to a wide range of climatic conditions, soil types, fertility levels, use patterns and management strategies. Red clover has a high yielding potential and cultivars grown in monoculture in humid climatic conditions can achieve in the second seasons over 80 t ha -1 of green mass yield and 15 t ha -1 of dry matter yield (Tucak et al, 2016). Red clover provides a high protein-rich feed for grazing livestock and during conservation is prone to the lower levels of protein degradation, compared to other legume feed sources (Phelan et al, 2015;Hart et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It is a short-term perennial legume that grows for about two to three years and is adapted to a wide range of climatic conditions, soil types, fertility levels, use patterns and management strategies. Red clover has a high yielding potential and cultivars grown in monoculture in humid climatic conditions can achieve in the second seasons over 80 t ha -1 of green mass yield and 15 t ha -1 of dry matter yield (Tucak et al, 2016). Red clover provides a high protein-rich feed for grazing livestock and during conservation is prone to the lower levels of protein degradation, compared to other legume feed sources (Phelan et al, 2015;Hart et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Unpredictable changes in weather conditions necessitate the need to conduct the research during two or more years to derive logical conclusion regarding genotype selection, especially when the experiments are conducted on the same geographical location (Ghodrati, 2013). The influence of climatic changes, particularly precipitation and temperature regimes have a direct and often negative influence on the quantity and quality of field crop yields (Kovačević et al, 2013;Tucak et al, 2016). The objectives of this research were to investigate yield components responsible for yield improvement and their relations during two seasons of opposite weather conditions, to determine the magnitude and the direction of the effect for each trait as well as their reaction to environmental stress.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the F. braunii hybrid grown in pure stand was the least sensitive to drought. According to Tucak et al (2016), high sensitivity of T. pratense grown in pure stand to drought, resulted in low yield of 23 cultivars and populations. Also Gaudin et al (2013) reported about the high sensibility of T. pratense in pure stand to drought.…”
Section: Discussionmentioning
confidence: 99%